Size-dependent structural and magnetic properties of chemically synthesized Co-Ni-Ga nanoparticles - Wang, Changhai; Levin, Aleksandr A.; Karel, Julie; Fabbrici, Simone; Qian, Jinfeng; Violbarbosa, Carlos E.; Ouardi, Siham; Albertini, Franca; Schnelle, Walter; Rohlicek, Jan; Fecher, Gerhard H.; Felser, Claudia (Nano Research, 2017)
Phase transitions and magnetic properties of shape-memory materials can be tailored by tuning the size of the constituent materials, such as nanoparticles. However, owing to the lack of suitable synthetic methods for size-controlled Heusler nanoparticles, there is no report on the size dependence of their properties and functionalities. In this contribution, we present the first chemical synthesis of size-selected Co-Ni-Ga Heusler nanoparticles. We also report the structure and magnetic properties of the biphasic Co-Ni-Ga nanoparticles with sizes in the range of 30–84 nm, prepared by a SBA-15 nanoporous silicatemplated approach. The particle sizes could be readily tuned by controlling the loading and concentration of the precursors. The fractions and crystallite sizes of each phase of the Co-Ni-Ga nanoparticles are closely related to their particle size. Enhanced magnetization and decreased coercivity are observed with increasing particle size. The Curie temperature (Tc) of the Co-Ni-Ga nanoparticles also depends on their size. The 84 nm-sized particles exhibit the highest Tc (≈ 1,174 K) among all known Heusler compounds. The very high Curie temperatures of the Co-Ni-Ga nanoparticles render them promising candidates for application in high-temperature shape memory alloy-based devices. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-04-14
Keywords: chemical synthesis; Co-Ni-Ga; magnetic properties; nanoparticles; size